Analysis of Human Physiology Learning for Semester I Students Using Discovery Learning Applications Based on Anchored Instruction at University - Susanto, Ratno; Rahayu, Dian; Fitria, Ully; Afandi, Achmad (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
The aim of this research is to produce physiology learning using discovery learning based on anchored instruction for first semester students of Physical Education, Health and Recreation at Nusa Cendana University. Human Physiology is a branch of biology that studies the working mechanisms of the human body, including how the body's organs function to support life. Learning Human Physiology requires an understanding of various systems in the human body, such as the nervous system, circulatory system, digestive system, and so on. This research aims to analyze the effectiveness of implementing the Discovery Learning method based on Anchored Instruction in learning Human Physiology for first semester students of Physical Education, Health and Recreation at Nusa Cendana University. The findings of this study indicate that the application of the Discovery Learning method based on Anchored Instruction in teaching Human Physiology to first semester students at universities has proven to be effective. The study is quasi-experimental (quasi-experimental) with pre-test and post-test. A class of first semester students studying Human Physiology at a university was the subject of the study; the researchers used existing classes as experimental groups due to limitations in determining random groupings of students